William Howard Taft's constitutional progressivism - Burns, Kevin (College teacher) (American political thought., 2021)
"Progressive Era scholarship has traditionally insisted that William Howard Taft was opposed to progressive reforms, emphasizing his "judicial temperament" and constitutional conservatism. Scholars have buttressed these theoretical arguments by pointing to Taft's break with Theodore Roosevelt and other notable progressives in the election of 1912. In contrast to this view, Kevin Burns argues that Taft's defense of the Constitution was not an attack on progressivism. Instead, Taft is better seen as a friendly critic of progressivism who worked to tie progressive policy initiatives to constitutional government. To the extent he broke with the radical wing of the Progressive Movement, he did so in order to show that progressive reform could be stronger and longer lasting if it was enacted by constitutional means. Burns makes a key distinction between policy and institutional reform. Taft was a progressive in terms of policy, but a conservative in his understanding of the Constitution. As president, he continued and expanded Theodore Roosevelt's work by breaking up trusts, formalizing land withdrawals for conservation, lowering tariffs, and expanding railroad regulations. Additionally, he worked to modernize the presidency by strengthening the chief executive's power and control over the executive branch and buttressing his power to lead the government as a whole. In contrast to more radical reformers, however, such as Herbert Croly, who insisted that the Constitution must be radically transformed in order to permit quick and effective progressive reforms, Taft hoped to advance reform through an evolution in politics and public policy, not a revolution in constitutional principles. By carefully analyzing his words and deeds as president and chief justice, Burns provides a new lens through which to view Taft. He shows that Taft presented a case for the continued viability of the Constitution, seeking to prove that our nation's fundamental law was (as he said) sufficiently "elastic" to be open to reform and change without itself changing"--